The System of Sociocultural Adaptation of Foreign Students at Leading Russian Universities (On the Example of Azerbaijani and Chinese Students) - V. Yu. Ledеneva; R. Abdullaev; L. Guseynova (Высшее образование в России)
The number of foreign students educating in Russian universities is increasing every year. With the growing number of such students, the issue of their adaptation becomes more re levant, because that adaptation also determines the success of education. The substantial role in this process falls to the share of universities and their educational system, which in the initial stages is aimed at accelerating the adaptation of foreign students to everyday life in Russia, also to provide high-quality and promising education.The article presents the results of a study conducted in order to investigate the features of sociocultural adaptation, the difficulties, which are faced by students during their education period and their expectations, coverage of the place and role of universities, therefore, and scientific and pedagogical staff. To achieve an accurate result, we conducted a survey of international students from the Republic of Azerbaijan and the People’s Republic of China studying at Russian universities. 107 students in total (45% Azerbaijani students and 55% Chinese students) from leading Moscow universities participated in the questionnaire-based survey, the age cohort of respondents ranged from 21 to 35 years. Analysis of the results of the survey made it possible to determine the main types of adaptation of students to identify objective and subjective factors of sociocultural adaptation, to compare the principal features of foreign students from Azerbaijan and China in order to understand the main problems of intercultural communication of students from different ethnic groups. The relevance and uniqueness of the study are based on cross-cultural differences between the studied groups, which made it possible to identify both principal and specific features, and their significant difference from Russian culture.The authors of the article concluded that the acceleration of the process of sociocultural adaptation is possible, first of all, through the study of the Russian language and pre-departure training in their homeland, which includes studying of Russian culture, history, traditions and specifics of intercultural communication. Based on the results of the study, the authors proposed recommendations for the formation of a system of measures aimed to optimize the processes of sociocultural adaptation, including well-organized training and teaching, as well as involvement of foreign students in the social activities of the university.